Oral Doxycycline on the Level of Matrix Metalloproteinase 9 in Rat Models Experiencing Traumatic Brain Injury - M, Faruk; K.R., Daud; A.A., Islam; A., Ihwan; A.A, Alfian Zainuddin (IIUM Medical Journal Malaysia, 2021)
INTRODUCTION: Cerebral edema in traumatic brain injury (TBI) results from hyperpermeability of the bloodbrain barrier (BBB). One of the causes in BBB permeability disorders is the activation of matrix metalloproteinase 9 (MMP-9) which can be inhibited by the administration of doxycycline. Knowing the role of oral doxycycline administration as an inhibitor of MMP-9 activation on the level of MMP-9 in cerebral edema in traumatic brain injury. MATERIALS AND METHODS: This study was an experimental study in Wistar rats with a post-test control design consisting of one control group, one group with provoked brain injury, and one group with provoked brain injury followed by oral doxycycline administration. RESULT: There were significant differences in the level of MMP -9 between the control group, the provoked brain injury group and the provoked brain injury group followed by oral doxycycline administration with p-value = 0.01 (p<0.05). CONCLUSION: Oral doxycycline administration can inhibit the increase of MMP-9 levels in cerebral edema in traumatic brain injury in Wistar rats.